2009
DOI: 10.1111/j.1537-2995.2009.02316.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell viability during platelet storage in correlation to cellular metabolism after different pathogen reduction technologies

Abstract: PRT treatment using M increased both anoxidative glycolytic flux and oxidative phosphorylation. The I-based technique was associated with an impaired mitochondria-based respiration. During terminal storage, this resulted in significantly lower maintenance of ATP and cell viability. The impact of these findings for storage prolongation or clinical use must await further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 34 publications
1
50
2
1
Order By: Relevance
“…[8][9][10] Mitochondrial membrane depolarization occurs in PCs during blood bank storage and further increases upon PI treatment. [11][12][13] Recently, we and other groups have demonstrated that apoptotic events including phosphatidylserine (PS) exposure, increased proapoptotic protein expression, and caspase activation are triggered by RF/UV treatment in stored PCs, further supporting the model that apoptosis is involved in development of the PLT storage lesion. 14,15 However, the detailed biochemical mechanism(s) triggered by RF/UV are still unclear.…”
mentioning
confidence: 82%
“…[8][9][10] Mitochondrial membrane depolarization occurs in PCs during blood bank storage and further increases upon PI treatment. [11][12][13] Recently, we and other groups have demonstrated that apoptotic events including phosphatidylserine (PS) exposure, increased proapoptotic protein expression, and caspase activation are triggered by RF/UV treatment in stored PCs, further supporting the model that apoptosis is involved in development of the PLT storage lesion. 14,15 However, the detailed biochemical mechanism(s) triggered by RF/UV are still unclear.…”
mentioning
confidence: 82%
“…Marschner/Goodrich spite the fact that mitochondrial DNA is fragmented by the treatment [11], the wavelength of UV light used in the process is distinct from the one where cytochrome C, FMN and FAD absorb (370-450 nm) [46], resulting in intact electron transfer processes within mitochondrial membranes. Low oxygen levels in the treated products are a simple measurement and indication of functional mitochondria, since oxygen is consumed and ATP produced during mitochondrial respiration [44,45]. Additional evidence that mitochondria are intact after Mirasol treatment comes from the use of PAS, in which acetate is used as a substitute for glucose.…”
Section: Pathogen Reduction and Leukocyte Inactivation Performancementioning
confidence: 99%
“…However, shearinduced adhesion is maintained in Mirasol-treated platelets [41][42][43], and mitochondrial function is preserved [44,45]. De- Overview of the Mirasol ® Pathogen Reduction Technology System 13 tween the Mirasol-treated and control group were detected for mean number of days between transfusions, mean number of platelet transfusions per patient and dose of platelets transfused.…”
Section: Mirasol Prt System For Plateletsmentioning
confidence: 99%
“…With this stain, polarized mitochondria appear red and depolarized green. Analysis of JC-1 fluorescence was performed using FACS analysis [27]. As also shown in our study, platelet storage causes a slight decrease in mitochondrial functionality.…”
Section: Resultsmentioning
confidence: 99%